Women and Political-Religious Fundamentalisms: An International Perspective - Mohideen, Reihana (Review of Women's Studies, 2009)
This paper presents three examples of political-religious fundamentalism: political Islam, communal fascism based on Hindu fundamentalism in India, and the Christian-fundamentalist right in the Bush administration in the US. It presents a political analysis of these movements, calling the readers' attention to the history and socio-political context to bring about an understanding of these phenomena as products of certain social and historical developments.